MINERALOGY, GEOCHEMISTRY AND ORIGIN OF ZINC-LEAD-BARITE DEPOSITS IN NORTHERN THRUST ZONE,NORTHERN IRAQ - Awadh , Salih; Habib, Habib; Al-Bassam, Khaldoon (Iraqi Journal of Science, 2024)
Four areas contain zinc - lead - barite deposits hosted by Cretaceous carbonate rocks are studied mineralogically, geochemically and genetically. These areas are Lefan, Lower Banik, Menin and Upper Banik, which are located northeast of Zakho city within Northern Thrust Zone, Northern Iraq.The deposits occur as small veins, scattered patches to disseminated ore, characterized by simple mineralogy consists of sphalerite, galena, little quantity of pyrite as primary sulfides and barite as primary sulfate. Most of sulfides are altered to their secondary minerals by supergene solutions.Paragenetic sequence of mineralization shows early and late sulfides generation deposited from hypogene solutions, and reveals reduction-oxidation potential fluctuation through nine stages of mineralization. The early generation of sulfides (sphalerite and galena) is characterized by replacement textures and high content of minor elements, while the late generation of sulfides is characterized by open space filling textures, and low content of minor elements.Geochemistry of bulk ore revealed the average ore grade up to 44.4% ZnO, and 4.1% PbO in Lefan, 27.4% ZnO, and 2.7% PbO in Lower Banik, 9.1% ZnO and 1.2 PbO in Menin, 1.9% ZnO and 20 ppm of Pb in Upper Banik.Fluid inclusions observed in barite contain heavy oil associated aqueous chloride-rich fluids (13% - 15.5% wt equv. NaCl). Formation temperature of barite is suggested to be 50-60 °C.The sulfur isotope composition (δ34S) of early generation galena is 0.36 per mil. This value is close to the hydrothermal magmatic sulfur origin, but the sulfur isotope compositions (δ34S) of late generation galena is 6.41 per mil. This value indicates that the hydrothermal magmatic fluids were partially mixed with oilfield brine connate waters. The sulfur isotope composition (δ34S) of barite ranges from 16.64 to 24.23 per mil indicating high isotopic fractionation caused by descending meteoric waters which diluted the ascending ore-bearing fluids. This case led to precipitation of barite in oxidizing conditions. The Lead isotope compositions (204Pb, 206Pb, 207Pb and 208Pb) of galena revealed that lead was derived from the crust reservoir.The elements (Zn, Pb, Fe, and Ba) may have originated from oilfield brine waters which may have partially mixed with hydrothermal fluids of magmatic origin supplying sulfur. These fluids may have been migrated upward as chloride and sulfide complexes along fractures and faults that they formed after crustal extension and rifting which took place by the effect of the Laramide Orogeny in the Upper Maastrichtian .The studied zinc-lead-barite deposits could be classified as epithermal, epigenetic strata-bound of Mississippi valley type (MVT) deposits, lithologically and structurally controlled within Cretaceous carbonate host rocks.